Development of an HPLC method using relative molar sensitivity for the measurement of blood concentrations of nine pharmaceutical compounds - Takashi Ohtsuki; Yi Huang; Ayane Kamiya; Yuki Nakayama; Miyuki Matsushita; Satoru Morikawa; Hiroshi Matsufuji (BMC, 2024)
Abstract We developed a reliable high-performance liquid chromatographic analysis method using a relative molar sensitivity (RMS) technique that does not require an authentic, identical reference analyte material to quantify blood serum carbamazepine, phenytoin, voriconazole, lamotrigine, meropenem, mycophenolic acid, linezolid, vancomycin, and caffeine levels for routine blood concentration measurements. Carbamazepine and caffeine were also used as non-analyte reference materials to calculate the RMS of each analyte. The RMS was calculated from the ratio of the slope of the calibration equation (analyte/non-analyte reference material), then used to quantify analytes in control serum samples spiked with carbamazepine, phenytoin, voriconazole, meropenem, mycophenolic acid, linezolid or vancomycin. In addition, the concentrations of these six drugs in control serum samples determined by the proposed RMS method agreed well with that obtained using a conventional method. The proposed RMS method is a promising tool for the clinical determination of nine drugs, given the accuracy, precision, and efficiency of quantifying these analytes.